Probing Ti–doped (Al–Ga) surface as Nanosensor for adsorbing the S- & N-containing heterocyclic compounds - Mollaamin, Fatemeh; Monajjemi, Majid (Art and Science Press Pte. Ltd., 2024)
Aluminum–Gallium doped with titanium by using ONIOM method through structural, electrical, and thermodynamic properties was studied in detail. Crystal structure of Ti–(Al–Ga) surface was coated by S- & N-heterocyclic carbenes of benzotriazole (BTA), 2-mercaptobenzothiazole (2MBT), 8-hydroxyquinoline (8HQ) and 3-amino-1,2,4-triazole-5-thiol (ATR). The “NMR” spectroscopy of the adsorption of BTA, 2MBT, 8HQ, and ATR on the Ti–doped Al–Ga nanoalloy surface represents that this surface can be employed as the magnetic S- & N-heterocyclic carbene sensors. In fact, “Ti” site in “Ti–(Al–Ga)” nanoalloy surface has bigger interaction energy amount from “Van der Waals’ forces” with BTA, 2MBT, 8HQ, and ATR that might cause them large stable towards coating data on the nanosurface. It has been estimated that the criterion for choosing the surface linkage of “S” and “N” atom in BTA, 2MBT, 8HQ, and ATR in adsorption sites can be impacted by the existence of close atoms of aluminum and gallium in the “Ti–(Al–Ga)” surface. The fluctuation of “NQR” has estimated the inhibiting role of BTA, 2MBT, 8HQ, and ATR for Ti–doped Al–Ga alloy nanosheet due to “S” and “N” atoms in the benzene cycle of heterocyclic carbenes being near the monolayer surface of ternary “Ti–(Al–Ga)” nanoalloy. Moreover, “IR” spectroscopy has exhibited that Ti–doped Al–Ga alloy nanosheet with the fluctuation in the frequency of intra–atomic interaction leads us to the most considerable influence in the vicinage elements generated due to inter–atomic interaction. Comparison to  amounts versus dipole moment has illustrated a proper accord among measured parameters based on the rightness of the chosen isotherm for the adsorption steps of the formation of BTA @Ti–(Al–Ga), 2MBT @Ti–(Al–Ga), 8HQ @Ti–(Al–Ga), and ATR @Ti–(Al–Ga) complexes. Thus, the interval between sulfur, nitrogen and oxygen atoms in BTA, 2MBT, 8HQ, and ATR during interaction with transition metal of “Ti” in “Ti–(Al–Ga)” nanoalloy, (N→Ti, O→Ti, S→Ti), has been estimated with relation coefficient of R² = 0.9509. Thus, the present has exhibit the influence of “Ti” doped on the “Al–Ga” surface for adsorption of S- & N-heterocyclic carbenes of BTA, 2MBT, 8HQ, and ATR by using theoretical methods. Furthermore, the “partial electron density” or “PDOS” has estimated a certain charge assembly between Ti–(Al–Ga) and S– & N–heterocycles of BTA, 2MBT, 8HQ, and ATR which can remark that the complex dominant of metallic features and an exact degree of covalent traits can describe the augmenting of the sensitivity of “Ti–(Al–Ga)” surface as a potent sensor for adsorption of BTA, 2MBT, 8HQ, and ATR heterocycles.